Reverse recruitment: The Nup84 nuclear pore subcomplex mediates Rap1/Gcr1/Gcr2 transcriptional activation - Menon, Balaraj B. (National Academy of Sciences, 2005)
The recruitment model for gene activation presumes that DNA is a platform on which the requisite components of the transcriptional machinery are assembled. In contrast to this idea, we show here that Rap1/Gcr1/Gcr2 transcriptional activation in yeast cells occurs through a large anchored protein platform, the Nup84 nuclear pore subcomplex. Surprisingly, Nup84 and associated subcomplex components activate transcription themselves in vivo when fused to a heterologous DNA-binding domain. The Rap1 coactivators Gcr1 and Gcr2 form an important bridge between the yeast nuclear pore complex and the transcriptional machinery. Nucleoporin activation may be a widespread eukaryotic phenomenon, because it was first detected as a consequence of oncogenic rearrangements in acute myeloid leukemia and related syndromes in humans. These chromosomal translocations fuse a homeobox DNA-binding domain to the human homolog (hNup98) of a transcriptionally active component of the yeast Nup84 subcomplex. We conclude that Rap1 target genes are activated by moving to contact compartmentalized nuclear assemblages, rather than through recruitment of the requisite factors to chromatin by means of diffusion. We term this previously undescribed mechanism “reverse recruitment” and discuss the possibility that it is a central feature of eukaryotic gene regulation. Reverse recruitment stipulates that activators work by bringing the DNA to an nuclear pore complex-tethered platform of assembled transcriptional machine components.